دراسة إمكانية التحطيم الحيوي لأنواع من المبيدات الكيميائية باستخدام بعض أنواع فطور التربة مخبرياً (Latakia University Journal -Biological Sciences Series, 2018)
أجري هذا البحث بعزل بعض أنواع فطور التربة من ترب معاملة بمبيدات زراعية مختلفة، إذ تم عزل الفطور التالية: Aspergillus niger (العزلتان A1، A2)، Fusarium oxysporum (العزلة F)، Trichoderma harzianum (العزلة T)، كذلك تم الحصول على الفطور التالية: F. solani (العزلة F7) وT. viride (العزلة T.v) من مختبر الدراسات العليا في كلية العلوم- جامعة تشرين، إذ كان تم عزلهما في بحثٍ سابق. اختبرت قدرة الفطور السابقة على التحطيم الحيوي لمجموعة من المبيدات وهي المبيد الحشري Dolan، والمبيد الحشري Plantocide، والمبيد النيماتودي Vydate، والمبيد الفطري Bayfidan من خلال اختبار تأثير ضعف الجرعة الموصى بها من المبيدات في الكتلة الحيوية للفطور المدروسة على وسط زراعي سائل PDB، بالإضافة إلى تحليل نواتج استقلاب المبيدات بواسطة مقياس الطيف الضوئي وقياس درجة pH الوسط. بينت النتائج أن أعلى كتلة فطرية على الأوساط السائلة المسممة بضعف الجرعة من المبيدات المدروسة كانت لعزلتي الفطر A. niger مع كل من المبيد النيماتودي والمبيد الحشري Dolan بدون فروق معنوية بينهما، إذ بلغت الكتلة الحيوية الفطرية للعزلة A1 (15.2 و14.9 غ)، على التوالي. بينما بلغت الكتلة الحيوية الفطرية للعزلة A2  (14.6 و14.8 غ)، على التوالي، مقارنةً مع الشاهد الذي بلغ للعزلتين المذكورتين (15.9 و15.2 غ)على التوالي. في حين كانت الكتلة الفطرية 0 غ و1.1 غ للعزلة F7 مع المبيدين السابقين على التوالي، مقارنةً مع الشاهد الذي بلغ (14.9 غ). كانت أعلى كتلة فطرية مع المبيد الفطري Bayfidan للعزلتين A1 وA2، وبلغت على التوالي (10.2 و9.3 غ)، تلاها بفرق معنوي كتلة كل من العزلتين T وF بقيم (5.6 و 4.2 غ)، على التوالي. أظهرت نتائج التحليل بجهاز مقياس الطيف الضوئي قدرة جميع الفطور المدروسة على تحليل المادة الفعالة ولجميع المبيدات المستخدمة، فقد كانت أعلى نسبة لتحلل المبيد النيماتودي مع العزلة A2 وبلغت (81.62 %)، وأقلها مع العزلة F7 وT.v وبلغت على التوالي (30.3 و32.24 %). أما بالنسبة للمبيد الفطري فقد كانت أعلى نسبة تحلل مع العزلة A1 وبلغت (70.2 %)، وأقلها مع العزلة F7 وبلغت (20.2 %). ومن جهةٍ أخرى بينت النتائج تأثير الفطور المدروسة في pH الوسط المسمّم بضعف الجرعة وجعله يتجه باتجاه الحامضية. وبنتيجة هذه الدراسة أظهرت الفطور المحلية المختبرة قدرةً واضحةً على التحطيم الحيوي للمبيدات الكيميائية المدروسة، الأمر الذي يدفع إلى المزيد من الدراسات والأبحاث في مجال التخلص من الملوثات حيوياً. The research was performed by isolating some species of soil- fungi from agricultural soils handling with different pesticides and fungicides. Where the following fungi were isolated: Aspergillus niger (The isolates A1 and A2), Fusarium oxysporum (The isolate F), Trichoderma harzianum (The isolate T). Also F. solani (The isolate F7) and T. viride (The isolate T.v) were used, whereas they were taken from high studies laboratory- Science Faculty- Tishreen University at a previous search. The research was conducted to assay the ability of the previous fungi to degradation a number of pesticides, the insecticide "Dolan", the insecticide "Plantocide", the nematicide "Vydate" and the fungicide "Bayfidan", through the effect of double dose of each pesticides in the biomass of the studied fungi on PDB medium. In addition to analysis the results residues of pesticides using Spectrophotometer, and evaluation the pH values. Results showed that the highest fungi mass on the poison medium was to the Aspergillus niger isolates with the nematicide and insecticide Dolan without significant differences between them. The fungi mass of A1 attained (15.2 and 14.9 g), respectively, and (14.6 and 14.8 g), respectively for the isolate A2, compared to the control treatment witch attained (15.9 and 15.2 g) for the two isolates. Where it was (0 and 1.1 g) for F7, respectively compared to (14.9 g) for the control treatment. The highest fungi mass with the used fungicide (Bayfidan) was to the isolates A1 and A2, which attained (10.2 and 9.3 g), respectively, followed significantly each of T and F with values reached to (5.6 and 4.2 g), respectively. Results of spectrophotometer showed the ability of all studied fungi to degradation the active material of all studied pesticides. The highest rate of degradation the nematicide was with A2 and attained (81.62 %), where the lowest was with F7 and T.v by (30.3 and 32.24 %), respectively. Whereas to the fungicide, the highest degradation rate was with A1 (70.2%), and the lowest was with F7 (20.2 %). On other hand, results showed the effect of studied fungi in pH the poison medium, and make it turn to be acidic. As a result of this study, the ability of the local fungi we used to biodegrade the used pesticides appeared definite, the thing drives us to perform more researches in biodegradation of pollutions.